International Cyber Crime: Main Trends - V. Puchkov, Denis (2021)
The subject of this article is global cybercrime. The relevance of the topic is increasing, as, globally, law enforcement agencies have noticed an increase in cyber crimes due to their use by organized individuals and criminal groups. The author comes to the conclusion that, in addition to the transformation of methods and techniques for committing cyber crimes, there is a change in the characteristics of cybercriminals themselves. In the article, the author notes that it is possible to observe major changes in the field of cyber threats against financial institutions and the emergence of new cybercriminal groups.